Raba sklonov v slovenščini in srbohrvaščini - Kalenić, Vatroslav (Slavistična revija, 1970)
Main characteristics of falls are given on the basis of contrastive analysis for Slovene and Serbo-Croatian languages. Identities and differences (given in tables) are established mainly upon data gathered from standard descriptive grammars of these languages.
Keywords: oblikoslovje; primerjalne študije; skloni; slovenščina; srbohrvaščina